Application of the Balanced Probability Theory to the Enforcement of Justice Using the Non-Conviction-Based Asset Forfeiture (Ncbaf) Mechanism from the Proceeds of Economic Crime in Indonesia - Yogaswara, Mohamad Bondan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Economic crimes according to Emergency Law no. 7 of 1955 is a criminal act that has an economic pattern or motive or which can have a negative influence on the healthy economic and financial activities of the State. Different from criminal acts in general, economic crimes in particular have their own characteristics that make them unique compared to ordinary criminal acts. The approach method used in this scientific work is Analysis and Evaluation of draft legal regulations regarding asset confiscation and the UNCAC international convention as well as other related legal regulations, namely juridical-normative by emphasizing the descriptive side as a method that seeks to provide an overview of the return of assets and recovery of the country's economy without having to completely deprive perpetrators of economic crimes of their human rights. Apart from that, the data collection method was carried out using library research, namely the study of documents from secondary data in the form of written legal materials, both primary legal materials in the form of related laws and regulations and secondary legal materials in the form of scientific books, articles in magazines, the internet. , newspapers, journals, and so on. Confiscation of assets without punishment or non-conviction-based asset forfeiture (NCB) can be the best solution to recover state financial losses from criminal acts of corruption. This is because the confiscation of NCB assets is the best application of the “Balanced Probability” theory. Through the confiscation of assets without punishment, the state obtains benefits in the economic sector by maximizing the return of state finances and justice in the legal sector by creating a form of punishment that provides a deterrent effect by making corruption no longer profitable and preventing the same criminal act from recurring by directly killing blood from The crime of corruption is money resulting from corruption